PENGUKURAN NILAI PANJANG KOHERENSI DUA SUMBER LASER MENGGUNAKAN INTERFEROMETER MICHELSON - Dhiesta Anggrainie; Minarni '; Tengku Emrinaldi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
One of the laser beam unique properties is its coherence. Each lasers has different coherence length. The coherence length of laser is very important in many photonic applications such as holography, spectroscopy, and interferometry. The coherence length can be measured by an interferometer. Measurement of coherence length of two HeNe lasers and two diode lasers has been done using a Michelson interferometer. Two HeNe lasers with same wavelength but from the different company and two diode lasers with different wavelength and brands were used. The laser used were HeNe laser 632,8 nm by Griffin (laser I), HeNe laser 632,8 nm by Pudak (laser II), diode laser 638 nm(laser III) and diode laser 405 nm (laser IV). Interference fringes from interferometer were recorded by a Thorlabs CCD camera and processed using ToupView software to determine the respective value of the maximum and minimum intensity of each fringe pattern. Data of the fringe pattern intensity were used to calculate the visibility (V) and coherence length (Lc) of the lasers. The results showed that Lc and deviation of laser I was (1,12±31,8× 10−3) mm, laser II was (0,99±61,6× 10−3) mm, laser III was(0,50±2,9× 10−3) mm and laser IV was (0,3 8±4,8× 10−3) mm, respectively . The results also showed that the coherence lengths of the HeNe lasers were greater than the diode lasers.